(untitled) (Medical Forum Monthly, 2023)
Objective: To determine the frequency of hypoglycemia in neonates admitted to the Neonatal Intensive Care Unit (NICU) at Ayub Teaching Hospital, Abbottabad. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the department of Neonatal Intensive Care Unit (NICU) at Ayub Teaching Hospital, Abbottabad from 05- Jan 2021 to 05-July 2021. Materials and Methods: Laboratory data, including blood glucose levels, were collected. Risk factors and signs of hypoglycemia were documented. Data was analyzed using SPSS 20.0. Results: The study included neonates with a mean age of 15.49±7.85 days. Of the patients, 46.76% were male and 53.24% were female. The mean gestational age at birth was 37.38±2.21 weeks. The mean glucose level at presentation was 76.63±22.55 mg/dl. Hypoglycemia was observed in 18.98% of patients, while 81.02% had normal glycemic levels. Risk factors included infants of diabetic mothers (51.22%), large for gestational age (9.76%), postdates birth (4.88%), premature birth (24.39%), and small for gestational age (9.76%). Conclusion: Although the frequency of hypoglycemia was not high, attention should be given to its management. Infants of diabetic mothers are at higher risk, necessitating increased care and surveillance after birth.